Depiction of Vishnu figure - Temples of India Project Team (Jio Institute, 2024)
Vishnu is depicted holding a shankha (conch) and a chakra (discus) in the upper arms, and a gada (mace) and kamandalu (water pot) in the lower hands. In some of the sculptures, instead of holding a kamandalu, he is depicted with his lower hand in varada hasta (boon-giving gesture).